Triceps-Sparing Total Elbow Arthroplasty for Distal Humerus Fracture: The Lateral Paraolecranon Approach. (August 2020) - Amini, Michael H.
Abstract : Summary: Distal humerus fractures in the elderly are a difficult problem to treat. Open reduction internal fixation has a high rate of complications, particularly because osteopenia compromises what is already tenuous fixation in a metaphyseal fracture. Total elbow arthroplasty is a more predictable outcome and easier recovery for these patients. However, most surgeons perform a low volume of total elbow arthroplasty. In addition, traditional exposure requires detachment of the triceps tendon. The lateral paraolecranon approach maintains the central tendon attachment to the olecranon while still facilitating relative ease of the procedure. Patients are allowed full active use of the triceps postoperatively, which is very helpful for polytrauma patients and those who are already dependent on assistive devices for ambulation.